Efficient Charge Separation between Bi and Bi2MoO6 for Photoelectrochemical Properties. Issue 17 (9th March 2016) - Ma, Ying; Jia, Yulong; Wang, Lina; Yang, Min; Bi, Yingpu; Qi, Yanxing
Abstract: Herein, porous Bi/Bi2 MoO6 nanoparticles have been prepared by a facile in‐situ reduction approach. Moreover, the morphology and Bi content of product could be controlled by varying the reaction time. By controlled fabrication, the desired porous Bi2 MoO6 nanostructure with incorporation of Bi was obtained and exhibited high photoelectric and photocatalytic activity. In particular, the samples yield a photocurrent density of 320 μA cm −2, which is 3.2 times that of the pure Bi2 MoO6 nanosheet (100 μA cm −2 ) under the same conditions. UV/Vis diffuse reflectance spectroscopy analysis confirmed the surface plasmon resonance in the as‐prepared porous nanoparticles. The improved photoelectric properties could be the synergistic effect of the porous structure with large surface area and effective electron‐hole separations between Bi and Bi2 MoO6 . Abstract : Porous Bi/Bi2 MoO6 nanoparticles have been synthesized by an in‐situ reduction method using molybdenum trioxide nanobelts and bismuth nitrate. In the reaction, MoO3 nanobelts not only serve as the molybdate source, but also the growth templates. The porous Bi/Bi2 MoO6 nanoparticles exhibit superior photoelectric activity to pure Bi2 MoO6 nanosheets and particles (see scheme).